Game-play characteristics differ between the European Super League and the National Rugby League: Implications for coaching and talent recruitment - Woods, C. T.; Leicht, A. S.; Jones, B.; Till, K. (International Journal of Sports Science & Coaching, 2018)
Objectives: To compare the game-play characteristics between the European Super League and the National Rugby League competitions. Methods: Eleven team performance indicators were extracted from each match played by every European Super League and National Rugby League team over their respective 2016 season. Data were averaged, classified according to competition (two levels: European Super League and National Rugby League) and modelled using univariate and multivariate techniques. Specifically, effect size statistics enabled between group comparisons, while non-metric multidimensional scaling enabled multivariate insights into competition dissimilarity. Results: Seven of the 11 performance indicators showed `large` to `very large` effects. Notably, National Rugby League game-play generated fewer `line breaks`, `errors`, `tackles` and `dummy half runs` relative to European Super League game-play (d>1.2). Despite the National Rugby League generating fewer `all runs` (d=1.27 [0.57-1.95]), game-play in this competition generated greater `all run distances` relative to the European Super League (d=1.78 [1.02-2.51]). Non-metric multidimensional scaling revealed clear multivariate competition dissimilarity, with European Super League and National Rugby League teams orienting distinctive positions on the ordination surface. Further, there was a greater spread in the relative positioning of National Rugby League teams compared to European Super League teams, indicating greater team dissimilarity within the National Rugby League. Conclusions: Our observations may be explained by differing competition rule interpretations, in addition to differing game strategies and player skill capabilities. Both coaches and talent recruitment managers associated with these competitions may consider our data to assist with the identification and recruitment of suitable players from these respective competitions.